Reimagining English language pedagogy in the post-COVID Era: Toward sustainable teaching practices - Asis-Ricamora, Maria Sharron De; Reynoso, Lino C.; Nuñez, Norma G.; Lorenzo, Lorenzo C.; Abejuela, Armando (Edelweiss Applied Science and Technology, 2025)
This qualitative study reimagines English Language Teaching (ELT) in the aftermath of the pandemic by examining how teachers responded to crisis-driven disruptions and by identifying sustainable practices that may inform and strengthen pedagogy in the years ahead. Four (4) informants from both public and private institutions participated in this research. Results show that the difficulties faced by teachers depended on their respective contexts, which were sub-coded into four (4) categories. Remediation strategies, along with the unlocking of new skills, were formulated and helped them thrive amidst the educational crisis they faced. Their circumstances also led them to suggest and realize the need to utilize appropriate strategies, methodologies, and tools in teaching English, such as exposure to ICT training, capacity-building, management support, revisiting pedagogy and mastery of content, enhancement of skills, and emotional support to learners. Ultimately, the teacher-informants expressed their visions and profound desires to move forward and accept the challenges with a positive goal in mind by forging new guidelines in English Language Teaching that may serve as sustainable practices in the post-pandemic era.